Meet me here - Bliss, Bryan (Greenwillow Books, 2016)
In a single night -- graduation night -- Thomas has to decide: Do what everyone has always expected of him? Or forge an entirely new path? Thomas is supposed to leave for the army in the morning. His father was Army. His brother, Jake, is Army -- is a hero, even, with the medals to prove it. Everyone expects Thomas to follow in that fine tradition. But Jake came back from overseas a completely different person, and that has shaken Thomas's certainty about his own future. And so when his long-estranged friend Mallory suggests one last night of adventure, Thomas takes her up on the distraction. Over the course of this single night, Thomas will lose, find, resolve, doubt, drive, explore, and leap off a bridge. He'll also face the truth of his brother's post-traumatic stress disorder and of his own courage.